The Determining Factors in Influencing Customer’s Loyalty: A Financial Approach - Hanafi, Syafiq Mahmadah (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
The research aims to evaluate customers’ loyalty to Sharia banking related to internal and external factors of the financial performance approach. A loyalty is depicted with Third-Party Savings deposited in Sharia banking. This study employed Autoregressive-Distributive Lag (ARDL) to explore the short period and the long period from variables’ relationships. The findings reveal that profit-sharing, administration fee, the interest rate of a conventional bank, inflation, and the total number of accounts (NOA) had significant effects on Third-Party Saving (TPS). They imply that the customer’s loyalty is internally established if there is a higher profit sharing in savings, lower administration fees, and total supplementary accounts. Yet, it is formed by external incentives, i.e., a lower interest rate of conventional banking and inflation.